1987
DOI: 10.1128/aac.31.3.434
|View full text |Cite
|
Sign up to set email alerts
|

Norfloxacin versus thiamphenicol for treatment of uncomplicated gonorrhea in Rwanda

Abstract: In an open prospective study, single oral doses of norfloxacin (800 mg) and thiamphenicol (2.5 g) were used to treat, respectively, 122 and 46 consecutive patients with uncomplicated gonorrhea. Neisseria gonorrhoeae was eradicated from 119 (97.5%) patients treated with norfloxacin and from 35 (76.0%) patients treated with thiamphenicol. Norfloxacin treatment failure was not related to drug resistance or to insufficient absorption of the drug. Thiamphenicol failure correlated with low in vitro susceptibility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
1993
1993

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Single doses of norfloxacin (61,638), ciprofloxacin (628,677,690,761), ofloxacin (15), and enoxacin (552,760,802) have all failed to prevent the development of postgonococcal urethritis in men, and in some studies a high frequency of persistence of Chlamydia trachomatis has been documented. More prolonged therapy for 7 to 10 days with norfloxacin (75) and ciprofloxacin (235) has also produced little or limited eradication of Chlamydia trachomatis in patients with nongonococcal urethritis.…”
Section: Sexually Transmitted Diseasesmentioning
confidence: 99%
“…Single doses of norfloxacin (61,638), ciprofloxacin (628,677,690,761), ofloxacin (15), and enoxacin (552,760,802) have all failed to prevent the development of postgonococcal urethritis in men, and in some studies a high frequency of persistence of Chlamydia trachomatis has been documented. More prolonged therapy for 7 to 10 days with norfloxacin (75) and ciprofloxacin (235) has also produced little or limited eradication of Chlamydia trachomatis in patients with nongonococcal urethritis.…”
Section: Sexually Transmitted Diseasesmentioning
confidence: 99%
“…Clinical studies have demonstrated that norfloxacin is effective in treating uncomplicated genital gonorrhea due to penicillin-sensitive and penicillin-resistant strains of Neisseria gonorrhoeae (5,10). It is more active in vitro against gonococci than tetracycline, the only other oral antimicrobial agent included in this study.…”
Section: Referencesmentioning
confidence: 93%
“…Infections caused by penicillinase-producing N. gonorrhoeae strains (3,4,9,11,15,27,30,38,39,46,48,50,55,56,60) and strains with chromosomally mediated resistance to penicillin (11) responded similarly to those caused by penicillin-susceptible strains.…”
Section: Clinical Efficacy In Genital Tract Infectionsmentioning
confidence: 98%
“…None of the currently available antimicrobial agents, including fluoroquinolones, is effective as a single dose in eradicating C. trachomatis genital infections, which most often occur as the syndrome of nongonococcal urethritis (NGU) or mucopurulent cervicitis. Studies which used single doses of norfloxacin (44), ciprofloxacin (30,43,48), ofloxacin (6,42), enoxacin (55,60), or fleroxacin (29) for the treatment of gonorrhea uniformly reported the substantial persistence of C. trachomatis or the development of postgonococcal urethritis (3,9,38,46,56), which is often caused by C. trachomatis.…”
Section: Clinical Efficacy In Genital Tract Infectionsmentioning
confidence: 99%